Novel cationic amphiphiles as delivery agents for antisense oligonucleotides. - DeLong, R K (1999)
There has been great interest recently in therapeutic use of nucleic acids including genes, ribozymes and antisense oligonucleotides. Despite recent improvements in delivering antisense oligonucleotides to cells in culture, nucleic acid-based therapy is still often limited by the poor penetration of the nucleic acid into the cytoplasm and nucleus of cells. In this report we describe nucleic acid delivery to cells using a series of novel cationic amphiphiles containing cholic acid moieties linked via alkylamino side chains. We term these agents 'molecular umbrellas' since the cationic alkylamino chains provide a 'handle' for binding of nucleic acids, while the cholic acid moieties are likely to interact with the lipid bilayer allowing the highly charged nucleic acid backbone to traverse across the cell membrane. Optimal gene and oligonucleotide delivery to cells was afforded by a derivative (amphiphile 5) containing four cholic acid moieties. With this amphiphile used as a constituent in cationic liposomes, a 4-5 log increase in reporter gene delivery was measured. This amphiphile used alone provided a 250-fold enhancement of oligo-nucleotide association with cells as observed by flow cytometry. A substantial fraction of cells exposed to complexes of amphiphile 5 and fluorescent oligo-nucleotide showed nuclear accumulation of the fluorophore. Enhanced pharmacological effectiveness of antisense oligonucleotides complexed with amphiphile 5 was observed using an antisense splicing correction assay that activates a Luciferase reporter. Intracellular delivery, nuclear localization and pharmacological effectiveness of oligonucleotides using amphiphile 5 were similar to those afforded by commercial cytofectins. However, in contrast to most commercial cytofectins, the umbrella amphiphile showed substantial delivery activity even in the presence of high concentrations of serum.